PARTISIPASI WANITA DALAM KEGIATAN USAHA KOPERASI UNIT DESA (KUD) - M LIES ENDARWATI (Jurnal Penelitian Humaniora, 2002)
Abstract This research attempts to see empirically women’s role in Rural Unit Cooperative Activities in gender perspective. The research population is all the members of Rural Unit Cooperation (KUD) in Daerah Istimewa Yogyakarta province. Data are obtained by using questionnaire in close and open format. The data analysis are performed using software SPSS by the univariate and bivariate descriptive technique. The conclusions of this study are as follows: (1) The participation level of women compared with men is qualitatively lower viewed from their status in KUD; (2) The factor promoting women to participate is that because KUD really helps in fulfilling the family economic needs, while for men because KUD really helps in fulfilling the needs of all members; (3) The factor hampering women to participate is that because KUD is not able to help in fulfilling the member’s needs;(4)The women opportunity to be a manager is greater than as an official chairperson, and higher than man; (5)the most acceptable leadership position as an official chairperson (6)Women still tend to be neglected in getting the opportunity to improve the personal quality in various form of training activities. Keywords: equally man and women (kemitrasejajaran), gender, rural unit cooperative activities, women’s participation